Beryllium determination in non-optimal matrices using the $^{9}$Be(d,n$γ )$$^{10}$B - Perdikakis, G.; Spyrou, A.; Kokkoris, M.; Zarkadas, Ch.; Karydas, A.-G.; Harissopulos, S.; Kossionides, S. (HNPS Advances in Nuclear Physics, 2021)
An alternative method for the detection of beryllium in light element matrices is proposed, implementing the use of a deuteron beam at energies from 1 to 2.1 MeV and the $^{9}$Be(d,n$γ )^{10}$B reaction. A HP GE detector of 20{%} relative efficiency was used to detect the 718 keV gamma ray of $^{10}$B. The minimum detection limits obtained for beryllium, are compared to those taken with other NRA techniques (PIGE, heavy-ion and charged-particle spectroscopy) in complex matrices containing high concentrations of light elements. The absolute $γ $-ray yield of the reaction is also compared to absolute $γ $-ray yields from literature.